Penguatan Daya Saing UMKM melalui Penerapan Konten Kreatif di Instagram pada Omee Digital Printing dan Konveksi - Laily, Ananda Khusnatul; Margareta, Ananda Alfira Margareta; Ilmi, Alfina Madinatul; Balqist, Amelia Alayda; Agustina, Aldila Aliffia Is Sya (Welfare : Jurnal Pengabdian Masyarakat, 2025)
The rapid development of digital technology has changed business competition, including for Micro, Small, and Medium Enterprises (MSMEs). Omee Digital printing and Konveksi, an MSME in Kediri, has faced challenges in optimizing digital marketing strategies, especially through Instagram. This community service program aims to strengthen Omee Digital printing’s competitiveness by implementing creative content marketing strategies on Instagram. The method used is the Participatory Action Research (PAR) approach, involving needs analysis, training, content creation, and strategy implementation. The results show a significant increase in Instagram engagement, follower growth, and customer interactions, positively impacting brand awareness and sales. Business owners also gained a better understanding of digital marketing techniques. This initiative demonstrates that optimizing Instagram as a marketing tool can enhance market reach and business sustainability. These findings can serve as a reference for other MSMEs to maximize digital marketing in the era of Industry 4.0.